THE ANALYSIS OF COMPUTERIZED ACCOUNTING SYSTEMS USAGE IN THE MICRO-SMALL ENTERPRISES - Alfonsa Dian Sumarna (AKUNTABILITAS, 2023)
This study aims to analyze demographic factors: understanding of SAK EMKM and motivation on Computerized Accounting System (CAS) usage in Indonesian MSEs. This study used online survey. Hypothesis testing through the t-test, ANOVA test, and Moderated Regression Analysis test. From the 87 respondents who did bookkeeping, there were 47,12% (41 respondents) using CAS and the remaining 52,88% (46 respondents) still using manual bookkeeping. From the 41 respondents who have using CAS consists of 87,8% (36 respondents) still using Microsoft Excel and the remaining of 12,2% use accounting software. The finding from this study show that only level education had a direct significant effect on CAS usage, while motivation did not moderate the relationship of the independent variables to CAS usage. Low level of education influence on the low CAS usage. But result for the simultaneous test without moderation and with moderation that the independent variables have a significant effect on the CAS usage